2018
DOI: 10.18063/som.v3i3.733
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of extreme ozone and heat waves in two cities from Morocco

Abstract: Temperature is the first meteorological factor to be directly involved in leading ozone (O3) extreme events. Generally, upward temperatures increase the probability of having exceedance in ozone adopted thresholds. In the global climate change context more frequent and/or persistent heat waves and extreme ozone (O3) episodes are likely to occur during in coming decades and a key question is about the coincidence and co-occurrence of these extremes. In this paper, using 7 years of surface temperature and air qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…Extreme events may be partly explained by these averages. This statement is in complete agreement with many other climatological and air pollution studies over the area [20,33,43,51].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Extreme events may be partly explained by these averages. This statement is in complete agreement with many other climatological and air pollution studies over the area [20,33,43,51].…”
Section: Discussionsupporting
confidence: 93%
“…This spotlights the role of the geographical location of the cities and the influence of meteorological parameters on events' occurrence. This influence was highlighted in many previous studies as well [1,6,7,[9][10][11]15,16,19,20,52]. For example, the study by Chen et al concluded that soaring ozone concentrations across China in 2017 could be mainly attributed to the notable change of meteorological conditions in 2017, characterized with rising temperature and sunshine duration and decreasing relative humidity [52].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations